Preparation method and application of Co confinement nucleation two-dimensional g-C3N4 catalytic membrane

By confined domain nucleation Co2+ in the two-dimensional g-C3N4 membrane, a two-dimensional g-C3N4 catalytic membrane with confined domain nucleation was constructed, which solved the problems of insufficient exposure of catalytic sites in the PMS activation and pollutant degradation of traditional catalysts, and achieved efficient PMS activation and antibiotic degradation.

CN119633869APending Publication Date: 2025-03-18XUZHOU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411811077.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the process of PMS activation and pollutant degradation, traditional heterogeneous catalysts have problems such as insufficient exposure of catalytic sites, slow mass transfer at the interface, difficult catalyst recovery and long reaction periods.

Method used

A two-dimensional g-C3N4 catalytic film with Co domain nucleation is used to retain Co2+ cations in the stacked channels in the two-dimensional g-C3N4 membrane through electrostatic adsorption, and the domain nucleation of Co2+ is achieved by adjusting pH and hydrothermal reaction temperature, thereby building a catalytic film with high permeability flux and catalytic activity.

Benefits of technology

Efficient PMS activation and antibiotic degradation are achieved, which significantly improves the dispersion and exposure level of catalytic sites, and overcomes the technical problems of traditional catalytic membranes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633869A_ABST
    Figure CN119633869A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a Co confinement nucleation two-dimensional g-C3N4 catalytic membrane, the preparation method is based on confinement nucleation in a metal cation membrane, two-dimensional g-C3N4 is used as a substrate, Co < 2 + > is electrostatically adsorbed through a superposing channel in the membrane with surface negative charges, and then the Co < 2 + > is subjected to confinement nucleation in the membrane through a hydrothermal reaction. Compared with a traditional catalytic membrane preparation method, the method has the advantages that the orderliness of stacked channels in the membrane is reserved to a great extent, and the nano confinement effect is effectively triggered while the membrane permeability is maintained, so that the Co confinement nucleation two-dimensional g-C3N4 catalytic membrane realizes efficient activation of PMS to remove antibiotic pollutants in water. The Co confinement nucleation two-dimensional g-C3N4 catalytic membrane prepared by the method disclosed by the invention realizes an efficient and stable PMS activation effect, so that efficient degradation of antibiotic pollutants in a water body is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation method and application of a two-dimensional g-C3N4 catalytic membrane with Co confined nucleation, and specifically to a preparation method and application of a two-dimensional g-C3N4 catalytic membrane with Co confined nucleation suitable for efficiently activating PMS to degrade antibiotics in water. The present invention belongs to the field of catalytic membrane material preparation and relates to the field of PMS catalysis. Background Art

[0002] At present, Fenton-like catalytic technology, as one of the advanced oxidation processes (AOPs), has been effectively applied in wastewater deep treatment and antibiotic pollution control. Heterogeneous persulfate activation technology shows excellent application potential, and its advantages include: easy transportation and storage of oxidants, sulfate radicals (SO4 ·- ) High oxidation potential (E0 = 2.6-3.1V NHE )、SO4 ·- The half-life is long (30-40μs), the metal leaching amount is small and the pH operating range is wide (pH = 2-8). The peroxide bond in the asymmetric molecular structure of peroxymonosulfate (PMS) is more easily broken to generate SO4 ·- Therefore, PMS activation is considered to be a wastewater purification technology with great application potential.

[0003] PMS activation can be carried out in a variety of ways, including UV activation, thermal activation and metal catalytic activation. Among them, transition metals have variable electronic structure and valence states, so they show high efficiency in PMS activation. Among many transition metals, Co has a special valence electron structure and high reactivity with PMS. It has been proven to be one of the most active metals for PMS activation. Therefore, many Co-based catalysts have been used as efficient catalysts for PMS activation for deep wastewater treatment and degradation of organic pollutants. However, the traditional heterogeneous reaction mode still has technical problems such as insufficient exposure of catalytic sites, slow interfacial mass transfer, difficult catalyst recovery and long reaction cycle.

[0004] The catalytic membrane system that couples heterogeneous catalysis with membrane filtration units has shown application potential in the field of deep wastewater treatment. The catalytic layer in the catalytic membrane is constructed by stacking catalysts. The channels in the membrane can promote the exposure of catalytic sites and the enrichment of reaction components, shortening the migration distance of the generated reactive oxygen species (ROS) to the target pollutants. At the same time, the confined space in the membrane can enhance the interfacial mass transfer and optimize the electronic structure, electron transport and reaction characteristics of the catalytic interface by triggering the nanoconfinement effect. At present, the preparation process of such catalytic membranes is usually divided into two steps, first preparing the finished catalyst and then loading it on the surface of the filter membrane to construct a catalytic membrane. During the catalyst preparation process, transition metals need to be calcined at high temperature for crystallization and nucleation, which may destroy the ordered morphology of the catalyst, which is not conducive to the construction of regular stacked channels in the membrane and reduces the permeability of the catalytic membrane. At the same time, metal species (main catalytic sites) tend to agglomerate during high-temperature crystallization and nucleation, which will inhibit the exposure of catalytic sites and ultimately reduce the overall performance of the catalytic membrane. Therefore, it is very necessary to develop a new catalytic membrane construction process to meet its high permeability flux and catalytic activity during PMS activation and pollutant degradation.

[0005] Studies have shown that the confined space structure of the catalyst carrier will produce a confinement effect on the internal nanoparticles, inducing the crystal growth process, regulating the water chemical properties, and changing the electron transfer process, thereby significantly affecting the catalytic process and performance of the catalyst. Studies on the confined nucleation of metal crystals have shown that confined space will affect crystal nucleation in many aspects, including crystal stability, growth orientation, and crystal face exposure. First, the confined space restricts the size of the crystal so that the nucleation is a metastable structure dominated by kinetics; secondly, the confined space will change the crystal interfacial tension and electrostatic effect to affect the growth orientation and crystal face exposure of the crystal nucleation, thereby optimizing the catalytic properties of the crystal face. The unique confined space in the membrane provides a place for the confined nucleation of metal crystals. Therefore, seeking appropriate nucleation metals and suitable preparation methods to develop catalytic membranes for confined nucleation of metal crystals is a technical problem that technicians in this field need to solve urgently. Graphitic carbon nitride (g-C3N4) has the advantages of special conjugated electronic structure, excellent chemical / thermal stability, simple preparation, low cost, and non-toxicity. Although g-C3N4 has been widely used in water treatment processes, there is still a lack of reports on constructing it into a catalytic membrane and applying it to activate PMS to degrade antibiotics in water, especially the research on g-C3N4 catalytic membrane based on Co confined nucleation. Summary of the invention

[0006] In view of the above technical problems, the object of the present invention is to provide a two-dimensional g-C3N4 catalytic membrane with Co confined nucleation suitable for efficiently activating PMS to degrade antibiotics in water.

[0007] Another object of the present invention is to provide a method for preparing the catalytic membrane. Another object of the present invention is to provide an application of the catalytic membrane, specifically to an application of efficiently activating PMS to degrade antibiotics in water.

[0008] The purpose of the present invention can be achieved through the following technical solutions:

[0009] A method for preparing a two-dimensional g-C3N4 catalytic film with Co confined nucleation, first preparing a two-dimensional g-C3N4 film, and then 2 + As a metal source, Co 2+ The cations are retained in the stacked channels of the two-dimensional g-C3N4 membrane with negative surface charge, and the Co 2+ Confined nucleation.

[0010] The method for preparing the two-dimensional g-C3N4 catalytic film with Co confined nucleation of the present invention comprises the following steps:

[0011] 1) The two-dimensional g-C3N4 is uniformly dispersed in ultrasonically treated deionized water to obtain a dispersion, the two-dimensional g-C3N4 is loaded on the surface of the PVDF membrane by vacuum filtering the dispersion, and the two-dimensional g-C3N4 is vacuum dried at 60° C. to obtain a two-dimensional g-C3N4 membrane;

[0012] 2) a certain amount of Co(NO3)2·6H2O is dispersed in ultrasonically treated deionized water, the pH of the solution is adjusted using NaOH, and the resulting solution is placed in a membrane filtration device equipped with the two-dimensional g-C3N4 membrane prepared in step 1) to obtain a catalytic membrane precursor;

[0013] 3) placing the catalyst membrane precursor in a drying oven at 120-200° C. for hydrothermal reaction for a certain period of time, then washing and filtering with deionized water, and vacuum drying at 60° C. to obtain a catalyst membrane.

[0014] As a preferred embodiment of the present invention, the two-dimensional g-C3N4 is prepared by the following method:

[0015] Melamine is placed in a covered crucible and wrapped with tin foil, placed in a muffle furnace and heated to 400-600°C at 5-10°C / min and calcined for 2-4 hours to obtain block g-C3N4; two-dimensional g-C3N4 is further prepared by thermal stripping, specifically, the block g-C3N4 is fully ground, placed in a covered crucible again and wrapped with tin foil, heated to 300-500°C at 5-10°C / min and calcined for 1-3 hours to obtain two-dimensional g-C3N4.

[0016] As a preferred embodiment of the present invention, the loading amount of the two-dimensional g-C3N4 on the PVDF membrane in step 1) is 0.5-3.0 mg / cm 2; The mass ratio of two-dimensional g-C3N4 to deionized water in the two-dimensional g-C3N4 dispersion is 1:2000-4000.

[0017] As a preferred embodiment of the present invention, the power of the ultrasonic treatment in step 1) is 150-300 W, preferably 200 W, and the time is 30-90 min.

[0018] As a preferred embodiment of the present invention, in step 2), Co 2+ The mass ratio to g-C3N4 is 1:10-30.

[0019] As a preferred embodiment of the present invention, in step 2), NaOH (0.1 M) is used to adjust the pH range to 9-11.

[0020] As a preferred embodiment of the present invention, the solution filtration rate in step 2) is 5-20 mL / min.

[0021] As a preferred embodiment of the present invention, the hydrothermal reaction temperature in step 3) is 120-200° C. and the reaction time is 12-24 h.

[0022] As a preferred embodiment of the present invention, the deionized water filtration rate in step 3) is 5-20 mL / min.

[0023] As a further preferred embodiment of the present invention, the preparation method comprises the following steps:

[0024] 1) Melamine was placed in a covered crucible and wrapped with tin foil, and then placed in a muffle furnace and heated to 550°C at 5°C / min and calcined for 3 h to obtain block g-C3N4; the block g-C3N4 was fully ground and then placed in a covered crucible again and wrapped with tin foil, and then heated to 500°C at 5°C / min and calcined for 2 h to obtain two-dimensional g-C3N4;

[0025] 2) A certain amount of two-dimensional g-C3N4 was uniformly dispersed in deionized water treated with 200W ultrasound, and the obtained suspension was vacuum filtered to load the two-dimensional g-C3N4 on the surface of the PVDF membrane, and vacuum dried at 60°C for 12h to obtain a two-dimensional g-C3N4 membrane;

[0026] 3) A certain amount of Co(NO3)2·6H2O was placed in 50 mL of deionized water treated with 200 W ultrasound, the pH of the solution was adjusted to 9-11 by NaOH (0.1 M), and the solution was placed in a membrane filtration device equipped with a two-dimensional g-C3N4 membrane and filtered at 5 mL / min to obtain a catalytic membrane precursor;

[0027] 4) The catalyst membrane precursor is placed in a drying oven at 120-200° C. for hydrothermal reaction for 12-24 h, filtered twice with deionized water at 5 mL / min, and vacuum dried at 60° C. to obtain a catalyst membrane.

[0028] The two-dimensional g-C3N4 catalytic film with Co confined nucleation is prepared according to the preparation method. The composition formula of the two-dimensional g-C3N4 catalytic film with Co confined nucleation is Co -x @g-C3N4 / PVDF (polyvinylidene fluoride), wherein x is Co 2+ During the preparation process, g-C3N4 was first prepared by calcining melamine, and then two-dimensional g-C3N4 was obtained by thermal stripping. Then, the two-dimensional g-C3N4 was loaded on the surface of the PVDF membrane by vacuum filtration. Then, Co 2+ The cations are retained in the stacked channels of the two-dimensional g-C3N4 membrane with negative surface charge. Finally, the Co 2+ Confined nucleation.

[0029] The application of the Co confined nucleation two-dimensional g-C3N4 catalytic membrane activated PMS to degrade antibiotics in water.

[0030] The main characteristic pollutants of the antibiotics are any one or more of tetracycline, norfloxacin, ofloxacin, and sulfamethoxazole; the concentration of the main characteristic pollutants is 5-20 mg / L.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The present invention provides a method for preparing a two-dimensional g-C3N4 catalytic membrane with Co confined nucleation suitable for efficiently activating PMS to degrade antibiotics in water. The preparation method is based on confined nucleation in a metal cation membrane. The method first prepares a two-dimensional g-C3N4 and obtains a two-dimensional g-C3N4 membrane by vacuum filtration; then, the superimposed channels in the membrane with negative surface charges are used to electrostatically adsorb Co 2+ Finally, the Co 2+ This method retains the orderliness of the stacked channels in the membrane to a great extent compared to the traditional catalytic membrane preparation method, maintaining the membrane permeability while effectively triggering the nano-confinement effect. At the same time, Co is adsorbed by electrostatic adsorption. 2+ , significantly improving the dispersion and exposure level of the catalytic sites in the membrane. In addition, the influence of the confined space in the membrane on the nucleation characteristics of Co crystallization strengthens the catalytic interface reaction. Therefore, the two-dimensional g-C3N4 catalytic membrane with Co confined nucleation achieves efficient PMS activation and antibiotic degradation, effectively overcoming the technical problems of heterogeneous reaction mode and traditional catalytic membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1:Preparation process and catalytic performance evaluation system of two-dimensional g-C3N4 catalytic membrane with Co confined nucleation (a: Preparation process flow chart of two-dimensional g-C3N4 catalytic membrane with Co confined nucleation; b: PMS activation of catalytic membrane and antibiotic degradation performance evaluation system)

[0034] Figure 1 aCo -0.05 In the preparation process of @g-C3N4 / PVDF, the two-dimensional g-C3N4 is first loaded on the surface of the PVDF membrane by vacuum filtration, and then the Co 2+ The Co crystals are retained in the negatively charged two-dimensional g-C3N4 membrane stacked channels, and finally the pH and reaction temperature are adjusted to confine the nucleation of Co crystals. Figure 1 In the PMS activation and antibiotic degradation performance evaluation system of the catalytic membrane of b, the mother liquor is a mixed solution containing antibiotic pollutants (5-20 mg / L) and PMS (0.2-2 mM), and the operating pressure is adjusted by nitrogen to control the membrane flux and filtration rate. In addition, the initial pH, coexisting substances and specific quenchers are all configured in the mother liquor.

[0035] Figure 2 :Structural characterization of two-dimensional g-C3N4 catalytic film with Co confined nucleation (a:Co -0.05 @g-C3N4 / PVDF surface SEM image; b: Co -0.05 @g-C3N4 / PVDF cross-sectional SEM image; c: Co -0.05 @g-C3N4 / PVDF cross-section mapping diagram; d: Co -0.05 @g-C3N4 / PVDF nitrogen adsorption-desorption and pore size distribution diagram)

[0036] Figure 3 :Physicochemical structure of two-dimensional g-C3N4 catalytic film with Co confined nucleation (a:Co -0.05 @g-C3N4 / PVDF XRD pattern; b: Co -0.05 @g-C3N4 / PVDF Co 2p diagram; c: Co -0.05 @g-C3N4 / PVDF O1s diagram; d: Co -0.05 @g-N1s graph of C3N4 / PVDF)

[0037] Figure 4 :Removal effect of two-dimensional g-C3N4 catalytic membrane with Co confined nucleation on antibiotic pollutants (a:,Co -0.05 @g-C3N4 / PVDF system for tetracycline removal efficiency; b: corresponding catalytic reaction kinetics)

[0038] Figure 5:Effects of different factors on the removal of antibiotic pollutants (a: PMS concentration, initial pH and coexisting substances; b: different antibiotic pollutants)

[0039] Figure 6 :Co -0.05 @g-C3N4 / PVDF / PMS system ROS identification (a: quenching experiment; b: DMPOX spectrum; c: TEMP- 1 O2 spectrum)

[0040] Figure 7 :Long-term operation performance of two-dimensional g-C3N4 catalytic membrane with Co confined nucleation (a: tetracycline removal efficiency and membrane flux change; b: Co leaching concentration) DETAILED DESCRIPTION

[0041] The present invention is further described in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0042] Example 1

[0043] Preparation of catalytic membrane: Weigh 39.25 mg of two-dimensional g-C3N4 and disperse it evenly in 100 mL of 200W ultrasonically treated deionized water for 60 min to obtain a dispersion, then filter the dispersion with a PVDF filter membrane (diameter 5 cm, pore size 0.1 μm) by vacuum filtration, and vacuum dry at 60°C to obtain a two-dimensional g-C3N4 membrane. Weigh 9.69 mg of Co(NO3)2·6H2O and disperse it evenly in 50 mL of 200W ultrasonically treated deionized water, then adjust the solution pH to 9.5 with NaOH (0.1M) solution, place the above mixed solution in a membrane filtration device equipped with a two-dimensional g-C3N4 membrane, and filter the mixed solution at a rate of 5 mL / min to obtain a catalytic membrane precursor. The catalytic membrane precursor was placed in a drying oven, hydrothermally reacted at 130°C for 20 hours, then filtered twice with deionized water at a rate of 5 mL / min and vacuum dried at 60°C to obtain a catalytic membrane of Co. -0.05 @g-C3N4 / PVDF.

[0044] Catalytic film characterization: Co observed by SEM -0.05 @g-C3N4 / PVDF surface and cross-sectional structure, the results are as follows Figure 2 a,b shown. Co -0.05 The surface of @g-C3N4 / PVDF is dense and porous, providing abundant channels for solution penetration. -0.05 The cross-section of @g-C3N4 / PVDF presents a typical two-dimensional layered structure, which is conducive to the exposure of internal catalytic sites and the interface contact of reaction components. -0.05 @g-C3N4 / PVDF cross-sectional distribution, the results are as follows Figure 2 c. Co, O, C and N elements are highly distributed in Co -0.05 The cross section of @g-C3N4 / PVDF shows that the Co species are densely distributed in the two-dimensional g-C3N4 membrane stacking channels, greatly enhancing the exposure of catalytic sites. -0.05 @g-C3N4 / PVDF pore structure, see Figure 2 d. Co -0.05 @g-C3N4 / PVDF presents a typical type IV adsorption-desorption isotherm, indicating that its interior is a mesoporous structure. -0.05 The pore size of @g-C3N4 / PVDF is concentrated in the range of 2-50nm, with a peak pore size of 3.25nm, indicating that Co -0.05 @g-C3N4 / PVDF has abundant nanochannels inside, which can trigger the nano-confinement effect when the catalytic reaction occurs. -0.05 @g-C3N4 / PVDF phase structure, the results are shown in Figure 3 a.Co -0.05 @g-C3N4 / PVDF has the characteristic diffraction of Co species while maintaining the original PVDF diffraction peak, corresponding to the crystal plane diffraction of Co3O4 and α-Co(OH)2, indicating that the Co species in the film mainly exist in the form of Co3O4 and α-Co(OH)2. -0.05 @ Chemical composition and element valence of g-C3N4 / PVDF, see Figure 3 bd. Figure 3 In b, the broad Co 2p peak is further deconvoluted to Co(III)2p 3 / 2 、Co(Ⅱ)2p 3 / 2 、Co(Ⅲ)2p 1 / 2 and Co(Ⅱ)2p 1 / 2 The peaks indicate that the valence state of Co in the film is variable and it mainly exists in the form of Co(Ⅱ) and Co(Ⅲ). Figure 3 In Figure 3c, the O1s peak can be divided into lattice oxygen, oxygen vacancies, and surface adsorbed oxygen (hydroxyl groups or water), among which oxygen vacancies can promote PMS adsorption and ROS generation during PMS activation. Figure 3 In d, the N 1s peak conforms to the typical g-C3N4 convolution peak, including N (NC = N), N-C3 and NH x , indicating that the addition of Co did not change the chemical structure of the g-C3N4 substrate.

[0045] Catalytic performance test: The Co -0.05The @g-C3N4 / PVDF implanted membrane filtration device is used to activate PMS for the degradation of tetracycline. The reaction conditions are as follows: the concentration of PMS is 0.6 mM, the concentration of tetracycline is 10 mg / L, the initial pH is 6.8, the reaction temperature is 25 °C, and the operating pressure of the membrane filtration device is 0.6 bar. As Figure 4 shown in a, within 30 min, Co -0.05 the removal efficiency of tetracycline by the @g-C3N4 / PVDF / PMS system reached 100%, and the control group excluded the catalytic effects of separate PVDF filtration and PMS itself, indicating that it was Co -0.05 the catalytic reaction of the @g-C3N4 / PVDF / PMS system that caused the degradation of tetracycline. At the same time, within 30 min, Co -0.05 the mineralization rate of tetracycline by the @g-C3N4 / PVDF / PMS system reached 66.9%. Figure 4 In b, according to the corresponding reaction liquid residence time and tetracycline removal efficiency, the first-order reaction kinetic constant of the Co -0.05 @g-C3N4 / PVDF / PMS system was as high as 0.066 m s -1 , indicating that the catalytic membrane had good PMS activation performance. Regarding the influence of different factors on the removal effect of antibiotic pollutants, Figure 5 in a, the tetracycline removal efficiency of the Co -0.05 @g-C3N4 / PVDF / PMS system increased with the increase of PMS concentration. However, when the PMS concentration increased from 0.4 mM to 0.6 mM, the Co -0.05 tetracycline removal efficiency of the @g-C3N4 / PVDF / PMS system reached 100%, indicating that the stacked channels and confined spaces in the membrane could enrich the reaction components and promote the contact of PMS with the catalytic sites to improve the ROS generation ability. Then, Co -0.05 the tetracycline removal efficiency of the @g-C3N4 / PVDF / PMS system within pH 3 - 9 was greater than 95%, indicating the good anti-pH interference ability of the catalytic membrane. At the same time, Cl - , HCO3 - , H2PO4 - , SO4 2- and the tetracycline removal efficiency in the presence of humic acid (HA) was inhibited to a certain extent (the removal efficiencies were 92.4%, 91.3%, 88.7%, 81.2% and 89.6% in turn). For inorganic anions, the reason for the inhibition was that Cl - , HCO3 - and H2PO4 - could react with SO4 ·- or · OH to generate weakly oxidizing Cl · , HOCl, HCO3 · and HPO4· etc., while SO4 2- The strongest inhibitory effect is attributed to its quenching of SO4 ·- and · OH and cannot continue to generate ROS. As a common natural organic matter (NOM) in natural water bodies, HA will compete with target pollutants to consume ROS, thereby reducing the removal efficiency of pollutants. Figure 5 b, Co -0.05 The removal efficiencies of @g-C3N4 / PVDF / PMS system for tetracycline, norfloxacin, ofloxacin and sulfamethoxazole were 100%, 99.6%, 99.8% and 98.7%, respectively, and the mineralization rates were 66.9%, 59.7%, 62.4% and 55.4%, respectively, indicating that the catalytic membrane has application potential in antibiotic wastewater treatment.

[0046] Catalytic mechanism analysis: Identification of Co by quenching experiments -0.05 @g-ROS in C3N4 / PVDF / PMS system, the results are shown in Figure 6 a. Co in the presence of methanol, tert-butyl alcohol (TBA), p-benzoquinone (p-BQ) and furfuryl alcohol (FFA) -0.05 @g-C3N4 / PVDF / PMS system had different degrees of inhibition on tetracycline removal efficiency. First, the tetracycline removal efficiency after methanol and TBA addition dropped to 47.4% and 65.5%, respectively, indicating that SO4 ·- and · OH is the key ROS for tetracycline removal. The tetracycline removal efficiency still reached 86.5% in the presence of p-BQ, indicating that · O2 - The effect of FFA on tetracycline removal was not significant, but the tetracycline removal efficiency declined sharply to 55.6% after the addition of FFA, indicating that 1 O2 is also Co -0.05 @The key ROS in g-C3N4 / PVDF / PMS system. Analysis of Co by EPR -0.05 @ROS types in the g-C3N4 / PVDF / PMS system, the results are as follows Figure 6 As shown in bc. Figure 6 In the DMPO spectrum of b, Co -0.05 The typical DMPOX signal of 1:2:1:2:1:2:1 appeared in the @g-C3N4 / PVDF / PMS system, which may be attributed to the rapid oxidation of DMPO adducts by oxidative free radicals or non-free radicals in the membrane, indicating that Co -0.05 @g-Highly available ROS inside C3N4 / PVDF. Figure 6 In the TEMP spectrum of c, Co -0.05 @g-C3N4 / PVDF / PMS system shows a typical 1:1:1 TEMP-1 O2 adduct signal, indicating 1 O2 is the key non-radical ROS responsible for the degradation of pollutants.

[0047] Stability test: The Co -0.05 @The operational stability of the g-C3N4 / PVDF / PMS system, including tetracycline removal efficiency, membrane flux variation, and Co leaching concentration. Figure 7 In a, Co -0.05 @g-C3N4 / PVDF / PMS system maintained nearly 100% tetracycline removal efficiency under 720min long-term continuous operation, the mineralization rate was maintained at 61.7%, and the membrane flux was higher than 500L / m -2 h -1 , there is no decline in catalytic performance and permeability performance; Figure 7 b, Co -0.05 The average Co leaching amount of the @g-C3N4 / PVDF / PMS system was 2.4 μg / L, indicating that there was almost no risk of metal leaching in the catalytic membrane.

[0048] Example 2

[0049] Preparation of catalytic membrane: Weigh 78.50 mg of two-dimensional g-C3N4 and disperse it evenly in 200 mL of 200W ultrasonically treated deionized water for 90 minutes to obtain a dispersion, then filter the dispersion with a PVDF filter membrane (diameter 5 cm, pore size 0.1 μm) by vacuum filtration, and vacuum dry at 60°C to obtain a two-dimensional g-C3N4 membrane. Weigh 25.84 mg of Co(NO3)2·6H2O and disperse it evenly in 50 mL of 200W ultrasonically treated deionized water, then adjust the solution pH to 10 with NaOH (0.1M) solution, place the above mixed solution in a membrane filtration device equipped with a two-dimensional g-C3N4 membrane, and filter the mixed solution at a rate of 5 mL / min to obtain a catalytic membrane precursor. The catalytic membrane precursor was placed in a drying oven, hydrothermally reacted at 150°C for 18 hours, then filtered twice with deionized water at a rate of 5 mL / min and vacuum dried at 60°C to obtain a catalytic membrane of Co. -0.067 @g-C3N4 / PVDF.

[0050] Catalytic performance test: The Co -0.067 @g-C3N4 / PVDF was placed in a membrane filtration device to activate PMS to degrade tetracycline. The reaction conditions were: PMS concentration was 0.6mM, tetracycline concentration was 10mg / L, initial pH was 6.8, reaction temperature was 25℃, and membrane filtration device operating pressure was 1.0bar. Within 30min, the tetracycline removal efficiency reached 98.4%, the mineralization rate reached 61.3%, and the membrane flux reached 417L / m 2h. Under 720min long-term continuous operation, Co -0.067 @g-C3N4 / PVDF / PMS system maintained a tetracycline removal efficiency of 96.1%, a mineralization rate of 54.9%, and a membrane flux of 404 L / m 2 h, the average Co leaching amount was 6.1 μg / L.

[0051] Example 3

[0052] Preparation of catalytic membrane: Weigh 29.44 mg of two-dimensional g-C3N4 and disperse it evenly in 100 mL of 200W ultrasonically treated deionized water for 60 min to obtain a dispersion, then filter the dispersion with a PVDF filter membrane (diameter 5 cm, pore size 0.1 μm) by vacuum filtration, and vacuum dry at 60°C to obtain a two-dimensional g-C3N4 membrane. Weigh 4.85 mg of Co(NO3)2·6H2O and disperse it evenly in 50 mL of 200W ultrasonically treated deionized water, then adjust the solution pH to 10.5 with NaOH (0.1M) solution, place the above mixed solution in a membrane filtration device equipped with a two-dimensional g-C3N4 membrane, and filter the mixed solution at a rate of 5 mL / min to obtain a catalytic membrane precursor. The catalytic membrane precursor was placed in a drying oven, hydrothermally reacted at 140°C for 24 hours, then filtered twice with deionized water at a rate of 5 mL / min and vacuum dried at 60°C to obtain a catalytic membrane of Co. -0.033 @g-C3N4 / PVDF.

[0053] Catalytic performance test: The Co -0.033 @g-C3N4 / PVDF was placed in a membrane filtration device to activate PMS to degrade tetracycline. The reaction conditions were: PMS concentration of 0.8mM, ofloxacin concentration of 10mg / L, initial pH of 6.8, reaction temperature of 25℃, and membrane filtration device operating pressure of 0.4bar. Within 30min, ofloxacin removal efficiency reached 98.1%, mineralization rate reached 59.4%, and membrane flux reached 577L / m 2 h. Under 720min long-term continuous operation, Co -0.033 @g-C3N4 / PVDF / PMS system ofloxacin removal efficiency maintained at 95.1%, mineralization rate maintained at 52.3%, and membrane flux maintained at 553L / m 2 h, the average Co leaching amount was 1.7 μg / L.

[0054] Example 4

[0055] Preparation of catalytic membrane: Weigh 39.25 mg of two-dimensional g-C3N4 and disperse it evenly in 100 mL of 200W ultrasonically treated deionized water for 60 min to obtain a dispersion, then filter the dispersion with a PVDF filter membrane (diameter 5 cm, pore size 0.1 μm) by vacuum filtration, and vacuum dry at 60°C to obtain a two-dimensional g-C3N4 membrane. Weigh 19.38 mg of Co(NO3)2·6H2O and disperse it evenly in 50 mL of 200W ultrasonically treated deionized water, then adjust the solution pH to 9.5 with NaOH (0.1M) solution, place the above mixed solution in a membrane filtration device equipped with a two-dimensional g-C3N4 membrane, and filter the mixed solution at a rate of 5 mL / min to obtain a catalytic membrane precursor. The catalytic membrane precursor was placed in a drying oven, hydrothermally reacted at 160°C for 22 hours, then filtered twice with deionized water at a rate of 5 mL / min and vacuum dried at 60°C to obtain a catalytic membrane of Co. -0.1 @g-C3N4 / PVDF.

[0056] Catalytic performance test: The Co -0.1 @g-C3N4 / PVDF was placed in a membrane filtration device to activate PMS to degrade tetracycline. The reaction conditions were: PMS concentration of 0.6mM, norfloxacin concentration of 10mg / L, initial pH of 6.8, reaction temperature of 25℃, and membrane filtration device operating pressure of 0.6bar. Within 30min, the removal efficiency of norfloxacin reached 96.4%, the mineralization rate reached 56.3%, and the membrane flux reached 498L / m 2 h. Under 720min long-term continuous operation, Co -0.1 @g-C3N4 / PVDF / PMS system maintained a norfloxacin removal efficiency of 95.1%, a mineralization rate of 51.2%, and a membrane flux of 484 L / m 2 h, the average Co leaching amount was 9.7 μg / L.

Claims

1. A method for preparing a two-dimensional g-C3N4 catalytic film with Co confined nucleation, characterized in that: The steps include: 1) The two-dimensional g-C3N4 is uniformly dispersed in ultrasonically treated deionized water to obtain a dispersion, the two-dimensional g-C3N4 is loaded on the surface of the PVDF membrane by vacuum filtering the dispersion, and the two-dimensional g-C3N4 is vacuum dried at 60° C. to obtain a two-dimensional g-C3N4 membrane; 2) a certain amount of Co(NO3)2·6H2O is dispersed in ultrasonically treated deionized water, the pH of the solution is adjusted using NaOH, and the resulting solution is placed in a membrane filtration device equipped with the two-dimensional g-C3N4 membrane prepared in step 1) to obtain a catalytic membrane precursor; 3) placing the catalyst membrane precursor in a drying oven at 120-200° C. for hydrothermal reaction for a certain period of time, then washing and filtering with deionized water, and vacuum drying at 60° C. to obtain a catalyst membrane.

2. The preparation method according to claim 1, characterized in that The two-dimensional g-C3N4 described in step 1) is prepared by the following method: The melamine is placed in a covered crucible and wrapped with tin foil, and then placed in a muffle furnace and heated to 400-600°C at 5-10°C / min and calcined for 2-4 hours to obtain block g-C3N4; two-dimensional g-C3N4 is prepared by thermal exfoliation; the method for preparing two-dimensional g-C3N4 by thermal exfoliation is as follows: the block g-C3N4 is fully ground, and then placed in a covered crucible again and wrapped with tin foil, and then heated to 300-500°C at 5-10°C / min and calcined for 1-3 hours to obtain two-dimensional g-C3N4; The loading amount of 2D g-C3N4 on PVDF membrane is 0.5-3.0 mg / cm 2 ; The power of ultrasonic treatment is 150-300W, and the time of ultrasonic treatment is 30-90min; the mass ratio of two-dimensional g-C3N4 to deionized water in the two-dimensional g-C3N4 dispersion is 1:2000-4000.

3. The preparation method according to claim 1, characterized in that Step 2) Co 2+ The mass ratio to g-C3N4 is 1:10-30.

4. The preparation method according to claim 1, characterized in that In step 2), the concentration of NaOH is 0.1 M, and the pH range is adjusted to 9-11.

5. The preparation method according to claim 1, characterized in that The solution filtration rate in step 2) is 5-20 mL / min.

6. The preparation method according to claim 1, characterized in that The hydrothermal reaction time in step 3) is 12-24h.

7. The preparation method according to claim 1, characterized in that In step 3), the deionized water filtration rate is 5-20 mL / min.

8. A two-dimensional g-C3N4 catalytic film with Co confined nucleation prepared according to the preparation method of any one of claims 1 to 7.

9. Application of the Co confined nucleation two-dimensional g-C3N4 catalytic membrane activated PMS as described in claim 8 to degrade antibiotic pollutants in water.

10. The use according to claim 9, characterized in that The main characteristic pollutants of the antibiotics are any one or more of tetracycline, norfloxacin, ofloxacin, and sulfamethoxazole; the concentration of the main characteristic pollutants is 5-20 mg / L.